Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Leaching of scandium from a basalt weathering crust-type scandium deposit: An alkali-acid combined treatment method - Xiaorui Wang; Ruidong Yang; Wei Cheng; Rong Chen; Jun Chen; Xinzheng Li (Minerals Engineering, 2026)

Bacterial cellulose guided In-Situ growth of ZIF-8 toward hierarchical N-doped porous carbon for enhanced CO2 capture - Shijie Wang; Xudong Zheng; Sifan Bao; Zihuai Xu; Zhouzhou Yang; Wei Sun; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Temperature-influenced deformation analysis of a full-scale steel-concrete-steel cable support tower model during construction - Zhi-Li Qi; Wei-Le Chen; Jian Li; Jian-Sheng Fan; Rong Xian; Fei Tian; Yu-Fei Liu (Engineering Structures, 2026)

Spiro-donor modified blue thermally activated delayed fluorescence emitters with high efficiency, narrowband emission, and excellent lysosomal targeting ability - Deli Li; Qingchao Liu; Ruizhe Xu; Wei Liu; Rong Hu; Wei Li; Shi-Jian Su; Ziyi Ge; Yuhua Tong (Chemical Engineering Journal, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Spatiotemporal dynamics of PFAS ecological risk in major Chinese river networks: a data-driven assessment (2011–2024) - Letian Zhang; Wei Lin; Zhouyun Xie; Yewei Wang; Rong Wu; Jiaqi Yang; Nanyang Yu; Xiaodong Li; Jie Liang (Water Research, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

The needs-solution-prototype-validation model: A feasibility study of nurse-led interdisciplinary collaboration in medical device innovation - Xiaodong Zhang; Fengli Wang; Aiying Gu; Haoyuan Li; Wei Wang; Yongchao Huo; Rong Xu; Yuanfeng Xue; Guohong Li; Yan Geng (Next Research, 2026)

TF2A ameliorates lipid metabolism in high fat diet mice as an oxidative derivative of EGCG with altered gut microbiota and hepatic transcriptomic profiles - Yiyun Zhang; Zongzhen Guo; Kefan Wei; Rong Li; Jiaqian Cao; Liang Zhao; Sujing Wu; Caili Feng; Qiliu Jiang; Yong Xue (Food Bioscience, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Biomimetic damping eutectic gels enabled by comonomer-regulated phase separation for motion-artifact-resistant bioelectrodes - Menghan Pi; Yichun Zhang; Zihe Liu; Wenhao Li; Min Li; Honglin Wu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

Strip feeding improves water quality, production performance and gut health of red swamp crayfish Procambarus clarkii by optimising feed spatial delivery - Yuchi Wang; Chao Guo; Kaiying Guo; Dengge Xu; Li Wu; Kuan Rong; Tanglin Zhang; Jiashou Liu; Wei Li (Aquaculture, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Decadal Resampling Reveals Widespread Increases in Soil Microbial Diversity Associated With Nitrogen Deposition - Yi Fan; Yiheng Tao; Bin Hua; Paul Kardol; Yakov Kuzyakov; Shuang Pang; Yi Wu; Tingling Li; Wei Yang; Honghui Wu; Anton A. Goncharov; Anastasia Yu. Korotkevich; et al. (Global Change Biology, 2026)
Simulated manipulation experiments, such as nitrogen addition to mimic atmospheric nitrogen deposition, are widely used in global change research. However, experimental manipulations may differ from real‐world environmental change in their intensity, duration, and co‐occurrence, leaving long‐term changes in soil microbial communities and soil health insufficiently understood. To address this gap, we resampled soils from 38 forest and grassland ecosystems across eastern China in 2009 and 2019 and assessed microbial taxonomic and functional diversity using shotgun metagenomics. Microbial diversity increased by 17% over the decade, accompanied by clear shifts in community composition. Among the environmental variables considered, nitrogen deposition (~19 kg nitrogen ha −1 year −1 across ecosystems) was the strongest predictor of changes in seven of 12 microbial community metrics. Larger nitrogen deposition was also associated with increased relative abundances of nitrogen‐cycling genes and reduced spatial turnover in microbial community composition. These effects were consistent with a potential alleviation of nitrogen limitation and weakening of deterministic community assembly, although these mechanisms could not be directly established. In addition, increases in genes associated with carbon degradation and phosphorus cycling, together with declines in the relative abundances of pathogens, antibiotic resistance genes, and DNA viruses, coincided with the raise of the composite soil health index. Our findings demonstrate widespread decadal increases in soil microbial diversity and soil health across eastern China, with nitrogen deposition emerging as their strongest environmental factor. These results highlight that microbial responses to long‐term ambient environmental change can differ markedly from responses inferred from short‐term or high‐intensity manipulation experiments.

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

Divergent responses of ecosystem water use efficiency to environmental drivers in arid versus humid regions - Hailing Li; Maohong Wei; Hongling Yang; Ya Hu; Shaokun Wang; Ping Yue; Xujun Ma; Fangwei Hao; Rong Ma; Xiaoan Zuo (Journal of Environmental Management, 2026)

Potential of RNAi targeting β-N-acetylglucosaminidase(NAG1)for controlling Dendroctonus valens LeConte (Coleoptera: Scolytidae) - Yue Sun; Qin Cao; Yong-Hao Nan; Yang-Nan Hou; Chun-Fang Qi; Ji-Gang Li; Jian-Rong Wei (Journal of Asia-Pacific Entomology, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Geomorphic filtering of pollen signals across a reef-to-basin transect and its implications for paleoenvironmental reconstruction in the Xisha archipelago, South China Sea - Jiani Chen; Sui Wan; Wei Li; Yi Zhong; Rong Xiang; Xiang Su; Chuanxiu Luo; Dizhu Cai (CATENA, 2026)

Heavy silicon isotope and mass-independent mercury isotope fractionation signals of Archean TTGs: Insights into the recycling of the silicified oceanic crust in the source region - Xiao Hu; Wenbin Zhu; Haizhen Wei; Runsheng Yin; Yongxiang Li; Yiwei Rong; Di Chen (Chemical Geology, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Cenozoic evolution of the Yangtze River, China: Constraints from quantitative detrital zircon UPb provenance modeling - Qiqi Song; Jie Hu; Zhiwu Li; Shengbiao Hu; Rong Tang; Chenghao Wei; Tianyao Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Mechanistic insights into triclocarban-induced skin barrier disruption via integrating imaging localization, multi-omics, and network toxicology - Jingwen Zheng; Run Guo; Rong Zhang; Xinyu Liu; Rouyue Guo; Haozheng Li; Juntong Wei; Yuxin Zheng; Hongna Zhang (Environmental Pollution, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Differential Enrichment of Deep Shale Gas in Southeastern Sichuan Basin: Dynamic Evolution and Preservation Mechanisms - Ke Zhang; Haikuan Nie; Songhang Zhang; Tianwu Xu; Zhujiang Liu; Chuanxiang Sun; Chengxiang Wan; Wei Dang; Pei Li; Jia Rong; Shuheng Tang (Journal of Earth Science, 2026)

Additive effects of heat and volatile organic compounds co-exposure on metabolic syndrome: evidence from petrochemical workers in China - Minhua Li; Rui Xu; Yilin Zhang; Shanshan Du; Rong Xu; Qing Zu; Zihu Lv; Wei Zheng; Weimin Ye; Jianjun Xiang (International Archives of Occupational and Environmental Health, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Non-stationary dynamic responses during continuous load transfer process of float-over installation: Experimental and numerical investigations - Yuhao Wei; Shuqing Wang; Xiancang Song; Gen Rong; Xiang Li; Yiyuan Yang (Ocean Engineering, 2026)

Organic fertilizer substitution combined with Bacillus velezensis SQR9 inoculation reduces carbon footprint and enhances net eco-economic benefits in tropical vegetable fields - Wei Tian; Huacheng Yin; Ziheng Zou; Rong Li; Yawen Huang; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; Jianwen Zou (Journal of Environmental Management, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Indole metabolites produced by Lactobacillus acidophilus impedes bisphenol F- aryl hydrocarbon receptor interaction and ameliorates bisphenol F induced depression-like changes - Miaoyang Hu; Ayiguzaili Manglike; Xiaozhu Li; Jin Wei; Xinyu Lou; Jing Liu; Zhiru Tang; Weiping He; Guixiang Ji; Wenjuan Wang; Tengfei Ma; Rong Gao; et al. (Journal of Hazardous Materials, 2026)

Proanthocyanidin/laccase-mediated cross-linking enhances the structural stability and rheological properties of collagen solutions - Junhong Xie; Li Feng; Fanghui Deng; Wei Yue; Wei Liang; Qiannan Zhao; Wentao Ma; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Dual-configuration arabinogalactan-II synergizes with rhamnogalacturonan-I in Lycium barbarum pectin to construct an intestinal anti-inflammatory glycan scaffold - Guoqiang Li; Yajun Qiao; Qiannan Wang; Xingfang Zhang; Lin Rong; Lixin Wei; Tingting Gao; Hongtao Bi (Carbohydrate Polymers, 2026)

Depth-coupling pattern between forest soil microorganisms and carbon mineralization in southwestern China - Shuang Ding; Shengzhao Wei; Honghong Lin; Li Rong; Enwei Zhang; Xue Yang; Huanxu Lv; Xingwu Duan (CATENA, 2026)

Novel Method for Preparing Pseudo-Male Common Carp by Inducing Secondary Female-to-Male Sex Reversal Under High Temperature Conditions - Yulai Wei; Yi Rong; Kuangxin Chen; Yongming Li; Yanlong Song; Binbin Tao; Ji Chen; Wei Hu (Marine Biotechnology, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

HGS+ enlarged vesicular compartments serve as the sites for coronavirus assembly at later infection stage - Xubing Long; Buyun Tian; Rongrong Chen; Rong Bai; Jinping Yang; Yushuang Fang; Xinyue Fu; Yanhong Xue; Wei Ji; Tao Xu; Zonghong Li (Science Bulletin, 2026)

Brain gray matter atrophy in adult population with cognitive impairment due to chronic cadmium exposure - Zhentao Gao; Longtao Yang; Rong Ma; Xiaoying Li; Fang Pei; Wei Hu; Yixuan Wu; Xiaojiang Tang; Jun Liu (NeuroToxicology, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Non-volumetric phase transition of PNIPAM enables high-sensitivity temperature monitoring and photoelectric therapy for wound care - Jie Ding; Danni Hou; Yuan Tian; Rong Li; Yuyan Wang; Junzhong Jiang; Yucai Hu; Chengheng Wu; Dan Wei; Jing Sun; Zi Qiao; Hongsong Fan (Chemical Engineering Journal, 2026)

From the perspective of resource recovery: Electrochemical treatment technology system for heavy metal complex wastewater - Rong Wang; Chenyang Zhang; Junyi Li; Wei Sun (Chemical Engineering Journal, 2026)

Aluminum modulation of cobalt states in perovskite for higher alcohols synthesis from syngas - Pengfei Song; Rong Liu; Zihan Shen; Yuwei Zhang; Xijun Li; Chenxi Zhang; Fei Wei; Yuan Liu; Chuan Wang; Zhichuan J. Xu (Chemical Engineering Journal, 2026)

Investigating the synergistic role of dual solid additives in morphology engineering and photogenerated charge dynamics for high-efficiency all-polymer solar cells - Liping Zhou; Tengxiang Gao; Shuonan Li; Wei Zhang; Rong Hu (Chemical Engineering Journal, 2026)

Nanoscale insights into the immobilization of coexisting As(V) and Cd(II) during Fe(II)-driven ferrihydrite transformation - Wei Li; Zhuohao Wu; Yang Lu; Rong Li; Qianying Sun; Zheng Liang; Wencheng Wu; Zhenqing Shi (Chemical Geology, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Evaluation of protein and metabolic engineering strategies on (−)-α-bisabolol production by Escherichia coli - Jiayi Ma; Rong Fang; Xiaoyuan Yue; Hui Jiang; Qixuan Kong; Tiankuo Jiang; Jiale Yu; Chang Zhou; Yuanyuan Xia; Wei Shen; Haili Liu; Yaqin Shen; et al. (Systems Microbiology and Biomanufacturing, 2026)

Mechanisms by Which Humic Acid Reduces Copper Toxicity in Citrus Roots Based on Omics and Physiology - Wei-Tao Huang; Rong-Rong Xie; Liang-Yuan Tong; Tian-Tian Xia; Jiuxin Guo; Ning-Wei Lai; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Plant Growth Regulation, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

Climate resilience of grain production in China: measurement, dynamic evolution, and spatial spillover effects - Mingliang Li; Rong Kong; Jiyu Wei; Yuanyuan Xiong; Guoxin Yu (Environment, Development and Sustainability, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Erosion obliges fungi to maintain community diversity through stochastic processes - Shuang DING; Shengzhao WEI; Li RONG; Xingwu DUAN (Pedosphere, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

Research progress on the structure of edible fungi polysaccharides and their anti-obesity mechanisms via the regulation of intestinal microbiota and metabolites - Xin Wei; Weiya Rong; Liyang Jin; Limin Zhang; Daoqin Ren; Yue Jiang; Jinling Cao; Shaojun Yun; Feier Cheng; Wenfei Zhao; Yong Li; Mingchang Chang; et al. (Food Bioscience, 2026)

Nitrogen doped graphene quantum dots modified a crystalline zinc phosphite based non-enzymatic electrochemical sensor for the ultra-low detection of tyramine - Pi-Chen Wei; Asit Kumar Panda; Yu-Chung Chang; Yi-Rong Li; Todd Hsu; Chih-Min Wang (Food Control, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Therapeutic effects of Gardenia jasminoides Ellis on salpingitis in laying hens: mechanisms of inflammatory regulation and egg quality improvement - Ruo-Yi Zhang; Hua-Lin Peng; Wei Zhang; Rong-Qiang Li; Hong-Jie Cui; Jian Li (Veterinary Research Communications, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Crop rotation benefits for nitrogen-oxide mitigation and soil health in tropical vegetable fields - Wei Tian; Feilong Liang; Rong Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; Jianwen Zou (Agriculture, Ecosystems & Environment, 2026)

Silencing NRBP1 Gene with shRNA Improves Cognitive Function and Pathological Features in AD Rat Model - Xinxue Wei; Xiaobei Liu; Yunqing Ban; Jing Li; Rong Huang (Biochemical Genetics, 2026)

Chronic heat stress attenuates innate immunity and increases susceptibility to Aeromonas hydrophila in Siberian sturgeon (Acipenser baerii) - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Wei Wang; Hua Zhu (Aquaculture International, 2026)

SVA virus-like vesicle vaccine based on VEEV-VSVG vector elicits efficient immune responses and protection in swine - Zhenxiang Rong; Mingjin Jiao; Nan Cao; Mingxing Lu; Shudan Liu; Chao Zhang; Liuqing Wei; Yamei Li; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Effect of structural characteristics of highland barley β-glucan by various thermal processing methods on intestinal microbial community and fermentative products - Rong Li; Ji Gao; Yiyun Zhang; Zijian Dai; Siqi Li; Tong Wu; Jiaqian Cao; Kefan Wei; Chao Wang; Qun Shen; Yong Xue (Food Bioscience, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

How human-perceived urban green spaces contribute to mental well-being: a machine learning approach - Enqi Cheng; Yuejing Rong; Yan Yan; Chenxing Wang; Lijie Wang; Yu Zhao; Zetong Wang; Wei Li (Journal of Environmental Management, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Amine modified porous carbon aerogel templated by the natural structure of wood for CO2 capture and selective separation - Zhouzhou Yang; Xudong Zheng; Zihuai Xu; Sifan Bao; Wei Sun; Shijie Wang; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2026)

Bionic cellulose fiber-based columnar solar evaporator with interfacial regulation for superfast water purification - Ying Qian; Zhexuan Lan; Shunfang Wen; Rong Liu; Haifeng Zhang; Ruiqing Li; Du Nie; Seeram Ramakrishna; Wei Zhang; Jiamu Dai (Desalination, 2026)

Boosting surface basicity of In2O3 aerogel for high-performance H2S sensors via an in-situ annealing strategy of carbon-composited In(OH)3 - Zheng Yang; Qian Rong; Wei Zhang; Qi Xu; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2026)

Ion−dipole−induced high stability of acidic DESs for efficient extractive and oxidative desulfurization - Dongao Zhu; Jie Yin; Siyi Han; Rong Zhang; Chunyan Dai; Jing He; Hongping Li; Wenshuai Zhu; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2026)

Decomplexation for resource recovery from heavy metal complex wastewater: mechanisms, challenges, and future roadmaps - Rong Wang; Chenyang Zhang; Shujuan Zhang; Wei Sun; Wenzhang Li (Chemical Engineering Journal, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

Novel 2-aminothiazole derivatives incorporating 9-alkyl purine moiety: design, synthesis, crystal structure, and bioactivity evaluation - Song Bai; Suran Wan; Miao Li; Rong Wu; Shouying Tang; Fang Wang; Lijun Chen; Xiaokang Lv; Xian Wei; Shuang Feng; Miaohe Zhang (Molecular Diversity, 2026)

Everything is everywhere, but everywhere is different: evidence from the phylogeography of asexual bdelloid rotifer Rotaria rotatoria species complex - Lingyun Zhu; Rong Huang; Sen Feng; Fan Gao; Meng Li; Hairong Lian; Zhizhong Li; Xinfeng Cheng; Mingbo Yin; Wei Zhang; Yilong Xi; Xianling Xiang (Hydrobiologia, 2026)

Fabrics of forsterite in CBa chondrite Sierra Gorda 013 - Rong Li; Wei Chen; Chun-Hui Li (Acta Geochimica, 2026)

Three new species of Scleroderma from Southern China - Ling Li; Hua Qu; Rong-Qian Bi; Rui Wu; Hai-Jiao Li; Zai-Wei Ge (Mycological Progress, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Efficient low-temperature NO reduction via constructing Cu+ −O−Co3+ sites to enhance lattice oxygen release and CO adsorption - He Wang; Ye Zhu; Wei Wang; Xiaoqing Dang; Yufei Zhang; Dandan Zhu; Rong Li; Dongjie Yan; Qian Ma; Jiaxin Qu; Jiaquan Zhang; Yu Huang (Journal of Hazardous Materials, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Development of green low-carbon denitrogenation process for EAF- reaction behavior and industrial performance of Ar-CH4 injection via hollow electrode - Xin Li; Guangsheng Wei; Ting Li; Shufeng Ye; Rong Zhu (Journal of Cleaner Production, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Synchronously interfacial fire retardancy and mechanical strengthening of glass fiber nylon 6 by temperature-responsive coupling agent - Han Li; Zhi Li; Rong Kuai; Wei-Zheng Zhang; Yanhao Huang; Qing-Wen Zeng; Zhi Hu; De-Yi Wang (Chemical Engineering Journal, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Quercetin Alleviates Postoperative Cognitive Dysfunction of Aged Mice by Regulating Microglial Polarization through Inducing miR-379-5p RNA Modification - Shu Rong Li; Long Wang; Yi Wei Li; Yi Xiao Li; Ren Wei Li; Zhi Fang Zhuo; Qing Hua Wu (Molecular Neurobiology, 2026)

Transcriptomics and Experiments Verified that Astaxanthin Reduces the Apoptosis of Nerve Cells in Ischemic Stroke by Inhibiting the Toll-like Receptor Signaling Pathway - Shan Gao; Jinjian Li; Yuetong Zhao; Zhen Wei; Chunshu Rong; Kuiyang Zuo; Xu Wang; Dexi Zhao (Molecular Neurobiology, 2026)

Cu–N4 active site sensing platform for point-of-care colorimetric detection of environmental organophosphorus pesticide - Rong Huang; Zhong Dong; Wanyi Zhang; Zhenggang Xue; Dongmei Deng; Wei Wang; Yuanyuan Li; Haibo He; Liqiang Luo (Analytica Chimica Acta, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)